2009
DOI: 10.1111/j.1468-2982.2009.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri-ictal Normalization of Visual Cortex Excitability in Migraine: an MEG Study

Abstract: To delineate if the change in cortical excitability persists across migraine attacks, visual evoked magnetic fields (VEF) were measured in patients with migraine without aura during the interictal (n = 26) or peri-ictal (n = 21) periods, and were compared with 30 healthy controls. The visual stimuli were checkerboard reversals with four different check sizes (15', 30', 60' and 120'). For each check size, five sequential blocks of 50 VEF responses were recorded to calculate the percentage change of the P100m am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 51 publications
(71 reference statements)
7
52
1
1
Order By: Relevance
“…This interpretation is in line with numerous evoked potential studies that have applied similar protocols (e.g. Afra et al, 1998;Ambrosini et al, 2003;Brodsky et al, 2013;Chen et al, 2009;Coppola et al, 2013b;Ozkul and Uckardes, 2002;Sand et al, 2008;Schoenen et al, 1995;Siniatchkin et al, 2006;Valeriani et al, 2003). The present study did not aim to investigate if the amplitude decline during VEP stimulation is caused by habituation in the central nervous system.…”
Section: Progressive Amplitude Changes During Recoding Of Vepsupporting
confidence: 71%
“…This interpretation is in line with numerous evoked potential studies that have applied similar protocols (e.g. Afra et al, 1998;Ambrosini et al, 2003;Brodsky et al, 2013;Chen et al, 2009;Coppola et al, 2013b;Ozkul and Uckardes, 2002;Sand et al, 2008;Schoenen et al, 1995;Siniatchkin et al, 2006;Valeriani et al, 2003). The present study did not aim to investigate if the amplitude decline during VEP stimulation is caused by habituation in the central nervous system.…”
Section: Progressive Amplitude Changes During Recoding Of Vepsupporting
confidence: 71%
“…[44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation. Deficient habitu ation was also subsequently described for several other modality specific evoked potentials: pattern reversal visual evoked potentials (VEPs), [33][34][35][36][37][38][39][40][41][42] visual evoked magneto encephalographic (MEG) responses, 43 auditory evoked potentials (AEPs), 51,52 and somatosensory evoked poten tials (SSEPs). [53][54][55] Several other studies, however, were not able to reproduce these results and found no habitu ation deficit in individuals with migraine, possibly because of differences in the methods used or selection of patients.…”
Section: Impaired Habituationmentioning
confidence: 92%
“…It is accompanied by initially decreased or normal amplitude of response after a small number of stimuli, followed by a stable amplitude, or even a transient amplitude increase (potentiation). [34][35][36][37][38][39][40][41][42][43] The first evidence for altered interictal habituation in patients with migraine came from studies of contingent negative variation (CNV), a slow event related corti cal response representing higher mental functions. [44][45][46][47] Subsequently, deficient habituation was demonstrated for another event related potential, P300, which is eli cited in the process of decision making after visual 48 or auditory 49,50 stimulation.…”
Section: Impaired Habituationmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be related to the changes in visual cortex responsiveness over the migraine cycle [20,22] and between episodic and chronic migraine [23]. For instance, during stimulus repetition, EEG and magnetoencephalographic visual evoked responses lack habituation in episodic migraine between attacks, but habituate normally during attacks and in chronic migraine [24,25,26]. Since the response pattern in chronic migraine is indistinguishable from that found during attacks in episodic migraine, it was suggested that chronic migraine patients are locked in an "ictal-like state" [23,27].…”
Section: Discussionmentioning
confidence: 99%